The M235T polymorphism in the angiotensinogen gene and heart failure: a meta-analysis. (June 2014) - Chen, Song; Zhang, Lan; Wang, Hong-Wei; Wang, Xiao-Yun; Li, Xue-Qi; Zhang, Li-Li
Background: The aim of the present study was to assess the association between M235T polymorphism and heart failure using a meta-analysis. Methods: A literature search of Google Scholar, PubMed, the Cochrane Library and the China National Knowledge Infrastructure database (January 1990–April 2012) was performed for relevant studies. Statistical analyses were carried out using the Stata 12.0 to combine all the relevant studies. Summary odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated in a fixed-effects model and a random-effects model when appropriate. The pooled ORs were performed under the allelic contrast (T vs M), the dominant (TT + MT vs. MM) and the recessive models (TT vs MT + MM). Begg's test was used to measure publication bias. Results: A total of six case-control studies including 842 patients and 1054 controls were enrolled in this meta-analysis. Overall, there was a significant association between angiotensinogen (AGT) gene M235T polymorphism and risk of heart failure in the subgroup analysis under the allelic contrast (T vs M: OR = 1.48, 95% CI: 1.04–2.11) and the dominant model (TT+MT vs MM: OR=1.67, 95% CI: 1.13–2.46) in the Caucasian population. Conclusions: The current meta-analysis suggests that M235T polymorphism might be associated with increased risk of heart failure in Caucasians.